How NATO Adapts : Strategy and Organization in the Atlantic Alliance Since 1950 - Johnston, Seth A. (Baltimore Johns Hopkins University Press, 2017)
"Today's North Atlantic Treaty Organization, with nearly thirty members and a global reach, differs strikingly from the alliance of twelve created in 1949 to "keep the Americans in, the Russians out, and the Germans down." These differences are not simply the result of the Cold War's end, 9/11, or recent twenty-first-century developments but represent a more general pattern of adaptability first seen in the incorporation of Germany as a full member of the alliance in the early 1950s
Include Bibliography and Index
Keywords: North Atlantic Treaty Organization History -- NATO -- Strategie